STUDI KASUS PADA PASIEN DENGAN GANGGUAN PERSEPSI SENSORI: HALUSINASI PENDENGARAN - Maryanto, Maryanto; Khafidin, Mukhamad; Rahmawati, Arni Nur (Coping: Community of Publishing in Nursing, 2023)
Hallucinations are a form of reality orientation disorder which is characterized by a person giving a response or assessment without any stimulus received by the five senses, and is one of the effects of perceptual disorders. The aim of this research is to provide nursing care to patients with auditory sensory perception disorders using dhikr and istighfar therapy. The method used by researchers is qualitative research using case studies with a nursing process approach to one of the patients who experienced sensory perception disorders. Data assessment was carried out by interviewing, observing and looking at the patient's medical records. Data analysis was carried out by data collection and data reduction. The research results showed that the patient was able to control his auditory hallucinations with dhikr and istighfar therapy. Spiritual Therapy with dhikr and istighfar, namely treatment aimed at curing mental illness, for each individual, with inner or spiritual strength, in the form of religious rituals rather than treatment with drugs, with the aim of strengthening a person's faith so that they can develop their potential and religious nature maximally, so it can be concluded that the application of dhikr and istighfar therapy can control the auditory hallucinations experienced by patients.